ANALISIS PENDAPATAN PETANI PADI MELALUI PROGRAM KREDIT USAHA RAKYAT DI DESA GAMBIRAN, KECAMATAN PRIGEN, KABUPATEN PASURUAN - Rahmawati, Eka Afrisa Salsabilah (Program Studi Ekonomi Pembangunan, 2023)
This study aims to analyze the income of rice farmers through the people's business credit program in Gambiran Village, Prigen District, Pasuruan Regency. The population in this study was rice farmers in Gambiran village. This study uses primary data with saturated sampling, with the provisions in this study as many as 75 people, meaning that all farmers are used as research samples. The data collection technique uses a questionnaire which then uses multiple linear regressions. The results showed that the variable land area, credit for business, and the number of workers had a significant positive effect on the income of rice farmers.